2021 IEEE International Conference on Image Processing (ICIP) 2021
DOI: 10.1109/icip42928.2021.9506427
|View full text |Cite
|
Sign up to set email alerts
|

Recalibrated Bandpass Filtering On Temporal Waveform For Audio Spoof Detection

Abstract: Deepfake techniques mislead people's cognition with highquality fake videos and audios, and speech synthesis is an important tool to implement cognitive attacks, which mainly include Text-To-Speech (TTS) and Voice Conversion (VC). In this paper, we propose a method for audio spoof detection based on frequency band recalibration via sinc convolution and squeeze-excitation module, extracting features from the temporal waveform and emphasizing the frequency bands that are more useful on this task. Experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Their results indicated that CQMCC outperformed most of the commonly used spoofing detection features. Ren et al used a method to obtain features from the temporal waveform using frequency band calibration via sinc convolution and squeeze-excitation module (Ren, et. al., 2021)).…”
Section: Related Workmentioning
confidence: 99%
“…Their results indicated that CQMCC outperformed most of the commonly used spoofing detection features. Ren et al used a method to obtain features from the temporal waveform using frequency band calibration via sinc convolution and squeeze-excitation module (Ren, et. al., 2021)).…”
Section: Related Workmentioning
confidence: 99%